Research progress of nanovaccine in anti-tumor immunotherapy - Yao, Min; Liu, Xiyu; Qian, Zhangbo; Fan, Dianfa; Sun, Xinjun; Zhong, Liping; Wu, Pan (Frontiers in Oncology, 2023)
Tumor vaccines aim to activate dormant or unresponsive tumor-specific T lymphocytes by using tumor-specific or tumor-associated antigens, thus enhancing the body's natural defense against cancer. However, the effectiveness of tumor vaccines is limited by the presence of tumor heterogeneity, low immunogenicity, and immune evasion mechanisms. Fortunately, multifunctional nanoparticles offer a unique chance to address these issues. With the advantages of their small size, high stability, efficient drug delivery, and controlled surface chemistry, nanomaterials can precisely target tumor sites, improve the delivery of tumor antigens and immune adjuvants, reshape the immunosuppressive tumor microenvironment, and enhance the body's anti-tumor immune response, resulting in improved efficacy and reduced side effects.Nanovaccine, a type of vaccine that uses nanotechnology to deliver antigens and adjuvants to immune cells, has emerged as a promising strategy for cancer immunotherapy due to its ability to stimulate immune responses and induce tumorspecific immunity. In this review, we discussed the compositions and types of nanovaccine, and the mechanisms behind their anti-tumor effects based on the latest research. We hope that this will provide a more scientific basis for designing tumor vaccines and enhancing the effectiveness of tumor immunotherapy.